Neural networks enable efficient and accurate simulation-based inference of evolutionary parameters from adaptation dynamics - Avecilla, Grace; Chuong, Julie N.; Li, Fangfei; Sherlock, Gavin; Gresham, David; Ram, Yoav (PLOS Biology, 2022)
This study shows that simulation-based inference of evolutionary dynamics using neural networks can yield parameter values for fitness and mutation rate that are difficult to determine experimentally, including those of copy number variants (CNVs) during experimental adaptive evolution of yeast.